Impact of the COVID-19 on Food Security and Sustainable Development Goals in India: Evidence from Existing Literature - SINGH, Ajay K.; KUMAR, Sanjeev; JYOTI, Bhim (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2022)
Prior to the COVID-19 pandemic, India’s food security was in a precarious state. The outbreak has further exacerbated the country’s food insecurity. In India, the COVID-19 pandemic has a detrimental influence on the food, nutrition, and health security of the poor, pregnant women, children, disadvantaged members of society, small and marginal farmers, daily wage earners, salespeople, and informal labourers. This study assesses the performance of India’s food security before and after the COVID-19 pandemic based on secondary data. This study further examines the impact of the COVID-19 pandemic on food security and SDGs in India based on existing studies. This study reveals that poverty, income inequality, hunger, child malnutrition, unemployment, health insecurity, women’s insecurity, gender disparity, and social inequality have increased in India due to the COVID-19 pandemic. For the aforementioned reasons, India will face some challenges in increasing production activities across the board. In India, the food security and income of vulnerable sections of society would be in peril. This study posits that due to the COVID-19 pandemic, it would be difficult for India to achieve the Sustainable Development Goals of no poverty (SDG1), zero hunger (SDG2), good health and wellbeing (SDG3), quality education (SDG4), gender equality (SDG5), clean water and sanitation (SDG6), decent work and economic growth (SDG8), industry, innovation, and infrastructure (SDG9), reduced inequality (SDG10), sustainable cities and communities (SDG11), and responsible consumption and production (SDG12). This study proposed some policy suggestions to help increase food security and achieve Sustainable Development Goals (SDGs) in India in the near future.